The Cross-talk between Tristetraprolin and Cytokines in Cancer - Guo, Jian; Wang, Hao; Jiang, Shiyi; Xia, Jiazeng; Jin, Shimao (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Cytokines are small secreted proteins serving as vital mediators that mediate the host immune responses. Transcription and post-transcription play a critical role in cytokine expression through the regulation of message RNA (mRNA) cytoplasmic localization, translation initiation and decay. Researches have been conducted to reveal regulatory mechanisms of cytokines production in cells involved in cancer. AU-rich element (ARE) can regulate the degradation and translation of mRNA by connecting with specific ARE binding proteins. It is now clear that tristetraprolin (TTP), as the most common ARE binding protein, negatively regulates many aspects of the cytokines through binding to the AREs in the 3'-untranslated region (3'UTR) of mRNA. Furthermore, some certain cytokines have an impact on TTP expression and function. Therefore, the cross-regulation between cytokines and TTP has come into sight. The complicated regulatory networks between cytokines and TTP are closely related to tumorigenesis. In this review, we summarize specific regulatory mechanisms of cytokine mRNAs. We focus on how TTP negatively regulates inflammatory and oncogenic cytokines expression after combining with AREs, we also pay attention to some cytokines mediating the expression of TTP and their cross-talk in various cancers in detail.
Keywords: ARE